Nexus between Personal Remittances, Financial Deepening, Urbanization, and Renewable Energy Consumption in Selected Southeast Asian Countries: Evidence from Linear and Nonlinear Assessment - Farzana, Nusrat; Qamruzzaman, Md; Islam, Yeasmin; Mindia, Piana Monsur (International Journal of Energy Economics and Policy, 2023)
This study examines the correlation between personal remittances, financial development, urbanization, and renewable energy utilization in Southeast Asian countries for the period 1991-2020. The study employs both linear and nonlinear analyses to examine the symmetric and asymmetric effects of these variables on renewable energy consumption. The results offer a plethora of significant insights. To commence, it is noteworthy that there exists an adverse correlation between financial deepening and the utilization of renewable energy, thereby challenging the prevailing notion that these two factors are positively interconnected. This demonstrates that the increasing financial growth in South Asian countries could potentially have adverse effects on the environment and hinder the implementation of renewable energy solutions. Furthermore, previous studies have demonstrated a positive correlation between urbanization and the utilization of renewable energy sources. The utilization of renewable energy technology is encouraged in cities due to factors such as population density, resource availability, and supportive legislation. Thirdly, personal remittances exhibit a varied impact, yielding favorable long-term consequences in Bangladesh and Pakistan, while conversely resulting in negative long-term effects in India and Sri Lanka. The findings indicate the necessity for governmental interventions aimed at mitigating the adverse effects of remittances, while simultaneously optimizing their positive influence on the utilization of renewable energy. Trade openness is positively correlated with long-term utilization of renewable energy, suggesting the potential for international trade in renewable energy resources. Nevertheless, it is worth noting that there is a negative correlation between trade liberalization and the utilization of renewable energy in the short term. This highlights the importance of implementing additional policy measures to address this issue. This study contributes to our comprehension of the intricate connections among personal remittances, financial deepening, urbanization, and energy consumption in Southeast Asian nations. It offers valuable insights for policymakers, researchers, and practitioners involved in advancing sustainable energy transitions and environmental sustainability.